LITERATURE REVIEW: THE INFLUENCE OF SELF-MANAGEMENT AND STRESS MANAGEMENT IN IMPROVING EMPLOYEE PERFORMANCE IN COMPANIES - Mayasari, Eka; Hasanah, Faidatul; Suhartini, Dwi (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2024)
This research aims to explore and reveal the importance of the influence of self-management and stress management in improving employee performance in companies or agencies. The research method uses a literature review approach, by collecting 15 journal articles from 2017-2023 from Google Scholar. The results of this research reveal the positive impact of self-management in achieving work goals, conflict management, and improving employee quality of life. Apart from that, the concept of stress management is an important key in living a balanced and healthy life in a world full of challenges. Stress is a natural response to pressure and demands routine life, but if not managed carefully, it can have detrimental impacts on a person's physical and mental well-being as well as an important basis for improving the work environment and employee welfare, which can increase productivity and performance. The research contribution can explain that the more stress management increases, the impact it will have on increasing employee performance. For this reason, there needs to be a balance between soft skills and hard skills. This research has limitations, namely the small number of journals reviewed due to the limited number of relevant topics.